Adsorption behaviour of the areca catechu husk ultrasonic assisted-phosphoric acid activated carbon on methylene blue dye / Nurul Iffah Mohd Said, Siti Nur Najwa Arman and Mohd Fauzi Abdullah - Mohd Said, Nurul Iffah; Arman, Siti Nur Najwa; Abdullah, Mohd Fauzi (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The production of activated carbon from agricultural waste is one of the most environmental-friendly solutions by converting agricultural waste into valuable material. In this study, Areca catechu husk is converted into activated carbon to remove methylene blue (MB) dye in aqueous solution. This Areca Catechu husk was impregnated with phosphoric acid (H3PO4) in an ultrasonic bath for 30 minutes to activate a pore surface before undergo carbonization at temperature of 700 ℃ for 2 hours. The physicochemical properties of the Areca catechu husk activated carbon was characterized by ash content, moisture content, bulk density, and iodine number. The result thus far shows that this activated carbon has low bulk density, low ash content and high iodine number that is very suitable for adsorption applications. The batch adsorption studies of MB dye were affected by adsorbent dosage, contact time, and initial concentration. The optimum parameters for the methylene blue adsorption were at adsorbent dosage of 0.06 g, initial concentration of 200 mg/L, and contact time of 180 minutes. According to the results of pHpzc and batch adsorption study, this Areca catechu husk activated carbon is suitable to remove cation dyes such as MB in neutral and alkaline solution. Therefore, activated carbon of Areca catechu husk can be produced inexpensively as the demand from commercial activated carbon market for adsorption of dye in water.